About Diana Umay (Journal of Alevism-Bektashism Studies, 2012)
Umay (also known as Umai or Mai; in Old Turkic: ) is the goddess of fertility and virginity in Turkic mythology and Tengriism and as such related to women, mothers and children. Umay resembles earth-mother goddesses found in various other world religions. literally in theMongolian language, "eje" or "eej" means "mother." in Mongolian "Umai" means womb or uterus. The earth was considered a "mother" symbolically.The Turkic root umay originally meant ’placenta, afterbirth’, and this word was used as the name for the goddess whose function was to look after women and children, possibly because the placenta was thought to have magic qualities. The name appeared in the 8th-centuryinscription of Kül Tigin in the phrase Umay teg ögüm katun kutıya ’under the auspices of my mother who is like the goddess Umay’.